Damage Characteristics and Mechanism of a Strong Water Inrush Disaster at the Wangjialing Coal Mine, Shanxi Province, China. (18th December 2018) - Fangpeng, Cui; Qiang, Wu; Shuai, Zhang; Ningan, Wu; Yuan, Ji
Abstract : A serious groundwater inrush occurred at the Wangjialing coal mine on March 28, 2010. Great effort from all over the country was taken during the postaccident rescue. However, triggered by accumulated water in the upper abandoned tunnels and goafs of a nearby closed individually owned coal mine, it caused great damage, including 38 deaths and direct economic losses of over 49 million yuan. The inrush water was from the abandoned tunnels and goafs, which were filled subsequently by groundwater from the sandstone aquifer in the roof of the coal seam. The passage formed in the west roof of the heading face of the air return tunnel in the 20101 first mining face. Unidentified distribution and water-filled degree of the abandoned tunnels and goafs are critical bases for the accident. That important regulations for abundant groundwater exploration and release were not carried out thoroughly was another fatal cause leading to the accident. The poor awareness of water hazard controlling also contributed to the accident to a large extent.